Habitual physical activity and central artery stiffening in older adults: the Atherosclerosis Risk in Communities study. Issue 9 (September 2018) - Tanaka, Hirofumi; Palta, Priya; Folsom, Aaron R.; Meyer, Michelle L.; Matsushita, Kunihiro; Evenson, Kelly R.; Aguilar, David; Heiss, Gerardo
Abstract : Introduction: Regular physical activity appears to attenuate or even reverse age-related arterial stiffening. Yet, it is not clear if the reduced stiffening associated with habitual physical activity is also observed in community-dwelling older adults. Methods: Among 3893 older adults in a prospective cohort study, we associated physical activity with measures of central arterial stiffness (via carotid–femoral pulse wave velocity or cfPWV) and pressure pulsatility (via central pulse pressure or cPP). We also examined the association of long-term habitual physical activity, measured as persistence in physical activity levels from mid-life to late-life, with cfPWV and cPP among 1747 participants. Results: The adjusted mean difference in cfPWV was lower, reflecting less arterial stiffness, for those with moderate ( ß  = −0.30 m/s) or high ( ß  = −0.38 m/s) physical activity compared with no physical activity. The adjusted mean difference in cPP was also lower for those with high ( ß  = −2.49 mmHg) physical activity, relative to no physical activity. Stronger effect estimates were observed among those with persistent physical activity from mid-life to late-life. Conclusion: Higher physical activity in late-life, and habitual physical activity from mid-life to late-life, is associated with lower central arterial stiffness and pressure pulsatility in a large population-based sample of community-dwelling older adults.